Religious Moderation Values in the Millennial Generation based on the Qur’an in Youtube Close The Door Habib Husein Ja’far al-Hadar - Prasetya, Panji; Nasrulloh, Nasrulloh (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
This study aims to analyze the values of religious moderation conveyed in the Login podcast program at Close The Door content, and to find out whether the content is able to facilitate the millennial generation in understanding the values of diverse moderation in everyday life. This type of research uses descriptive qualitative research, with data collection techniques, namely video content analysis of the Login podcast program at Close The Door, and documentation. The results of this research show that the values of religious moderation conveyed by Habib Ja'afar are very influential on the millennial generation, because they provide easy access, relevant messages, and practical guidance and strengthen religious understanding for the community. The conclusion of this study is that the message conveyed by Habib Ja'far is easy to understand and helps millennials gain a better understanding of religious teachings through podcasts on social media. The contribution of the article for the millennial generation is to provide deep insight into the values of religious moderation, as well as facilitate the millennial generation in understanding, accessing information, strengthening religious understanding and applying it in everyday life.